Exploring the potential of energy communities in the Italian territory - Brunoro, Silvia; Bizzarri, Giacomo; Boldrin, Enrica (Frontiers in Built Environment, 2024)
Renewable Energy Communities (REC) are clean -energy, emergent initiatives that invest in people cooperation in order to meet consumption needs and environmental goals. The main aim of the study is to explore the potential of Renewable Energy Community in Italy by identifying a methodological perspective to describe the development processes, to encourage the diffusion of multi-stakeholders' initiatives in the Italian territory.To do so, we purpose a general analysis of the Renewable Energy Communities framework, starting from the regulatory and technical-administrative state of the art that regulates Renewable Energy Communities in Italy, based on information's coming from literature. Then we interpret the procedure of REC initiatives by systematizing the steps of energy community forming and their characteristics, coming from literature review of experiences achieved at a national level.A vast literature is available on renewable energy technologies, but existing research lacks assessments regarding description of forming process of local energy systems applied to realized experiences. To do this, two strategies of energetic community are proposed, by a comparative case study analysis, to give a framework of the emerging phenomenon, to analyze and define the types of Renewable Energy Communities based on realized experiences in Italy.